Strategi Pengembangan Usaha Florist Nawanua Flora Di Kelurahan Kakakskasen Tiga Kota Tomohon - Wowor, Zefania Gracia; Kaunang, Rine; Taroreh, Melissa Lady Gisela (Sam Ratulangi University, 2023)
The aim of the study was to formulate a business development strategy for Florist Nawanua Flora in Kakaskasen Tiga Village, Tomohon City. The research lasted for 5 months, from May to September 2022. The method used in determining the sample was the Purposive Sampling method. The data used are primary data and secondary data. Primary data were obtained directly from respondents by conducting direct interviews using a prepared questionnaire. Secondary data was obtained from literature studies and agencies related to the data needed in the research. The analytical method used in this research is SWOT analysis. The results showed that based on the SWOT analysis, Florist Nawanua Flora's business development strategy is in quadrant 1, which means a strategy is needed to support the strengths and take advantage of the various opportunities that exist.